Neural networks in B-ISDN flow control: ATM traffic prediction or network modeling? - Neves, Joaquim José Santos Esteves (1995)
The authors discuss a technique that offers the combination of shared bandwidth and rejection rate parameters, together with the quality of service predicted by neural networks in a novel strategy for connection admission control and call routing.